The gift of the gab. Anthropology and conversation analysis - Zeitlyn, D; Zeitlyn, D (Anthropos Institute, 2004)
This paper discusses the fine-grain analysis of conversation and how conversational structure is related to larger issues of social organisation. Mauss's analysis of "the Gift" is related to "adjacency pairs" and the patterns of turn-taking that form conversational structure, particularly helping identification of conversational breakdown and subsequent repair. Social tensions cause problems in communication. Hence, the study of social actors keeping conversation flowing reveals social processes. Ethnographic examples are used from Mambila in Cameroon. The moral dimension to gift exchange can help us understand why dumb insolence is offensive. Failing to return a greeting is similar to the failure to return a gift. The exchange of words shows up the web of relationships that constitute the fabric of society.